Fitness Consequences of Innovation in Spotted Hyenas - Johnson-Ulrich, Lily; Benson-Amram, Sarah; Holekamp, Kay E. (Frontiers in Ecology and Evolution, 2019)
Innovation is a well-studied cognitive ability related to general intelligence, brain size, and behavioral flexibility. Innovative ability varies considerably within species and it is widely assumed that this variation must have important fitness consequences. However, direct evidence for a link between innovation and fitness has rarely been shown. Previous research examined variation in innovation in wild spotted hyenas when confronting a novel puzzle box baited with meat. The earlier work revealed that variation in innovation in spotted hyenas was not related to age, sex, or social rank, but was predicted by neophobia, persistence, and diversity of motor responses to the puzzle. Here, we used the same dataset from wild spotted hyenas to investigate potential links between innovation and fitness. We found that innovative hyenas had lower offspring survivorship than non-innovators, but higher annual cub production (ACP). To test the hypothesis that high ACP can compensate for low offspring survival, we also measured annual cub survivorship (ACS) counting only offspring that survived at least 1 year. Here, there was no significant difference between innovators and non-innovators, which suggests that higher ACP does compensate for lower offspring survival, at least to one year of age. Overall, our data suggest that innovation may have both costs and benefits for fitness in wild spotted hyenas.